Analysis of Microbiota-Host Communication Mediated by Butyrate in Atlantic Salmon - Maisey-Munoz, K; Tello-Reyes, M; Soto-Aguilera, S; Vargas-Cardenas, R; Flores-Kossack, C; Parra-Mardonez, N (Elsevier B.V., 2023)
Butyrate is a microbiota-produced metabolite, sensed by host short-chain fatty acid receptors FFAR2 (Gpr43), FFAR3 (Gpr41), HCAR2 (Gpr109A), and Histone deacetylase (HDAC) that promotes microbiota-host crosstalk. Butyrate influences energy uptake, developmental and immune response in mammals. This microbial metabolite is produced by around 79 anaerobic genera present in the mammalian gut, yet little is known about the role of butyrate in the host-microbiota interaction in salmonid fish. To further our knowledge of this interaction, we analyzed the intestinal microbiota and genome of Atlantic salmon (Salmo salar), searching for butyrate-producing genera and host butyrate receptors. We identified Firmicutes, Proteobacteria, and Actinobacteria as the main butyrate-producing bacteria in the salmon gut microbiota. In the Atlantic salmon genome, we identified an expansion of genes orthologous to FFAR2 and HCAR2 receptors, and class I and IIa HDACs that are sensitive to butyrate. In addition, we determined the expression levels of orthologous of HCAR2 in the gut, spleen, and head-kidney, and FFAR2 in RTgutGC cells. The effect of butyrate on the Atlantic salmon immune response was evaluated by analyzing the pro and anti-inflammatory cytokines response in vitro in SHK-1 cells by RT-qPCR. Butyrate decreased the expression of the pro-inflammatory cytokine IL-1β and increased anti-inflammatory IL-10 and TGF-β cytokines. Butyrate also reduced the expression of interferon-alpha, Mx, and PKR, and decreased the viral load at a higher concentration (4 mM) in cells treated with this molecule before the infection with Infectious Pancreatic Necrosis Virus (IPNV) by mechanisms independent of FFAR2, FFAR3 and HCAR2 expression that probably inhibit HDAC. Moreover, butyrate modified phosphorylation of cytoplasmic proteins in RTgutGC cells. Our data allow us to infer that Atlantic salmon have the ability to sense butyrate produced by their gut microbiota via different specific targets, through which butyrate modulates the immune response of pro and anti-inflammatory cytokines and the antiviral response. © 2023 The Authors